Improving the management of corporate culture on the educational services market - E. M. Hrapovitskaya; V. N. Borobov (Путеводитель предпринимателя, 2020)
In the scientific article discusses the features of the corporate culture of educational institutions. The strategy of formation of corporate culture. Available implementation mechanisms to change the corporate culture, occupying a key position in the management of corporate culture. Estimated potential for improving the management of corporate culture in the field of educational services.